Long-term Chinese milk vetch incorporation promotes soil aggregate stability by affecting mineralogy and organic carbon - Yulu Chen; Li Huang; Jusheng Gao; Zhen Zhou; Muhammad Mehran; Mingjian Geng; Yangbo He; Huimin Zhang; Jing Huang (Journal of Integrative Agriculture, 2025)
Soil aggregates profoundly impact soil sustainability and crop productivity, and they are influenced by complex interactions between minerals and organics. This study aimed to elucidate the alterations in mineralogy and soil organic carbon (SOC) following long-term green manure incorporation and the effect on soil aggregates. Based on 5- and 36-year field experiments, surface soil samples (0–20 cm) were collected from Alfisol and Ferrisol soils subjected to rice–rice–winter fallow (CK) and rice–rice–Chinese milk vetch (MV) treatments to investigate aggregate stability, mineralogy, SOC composition, and soil microstructural characteristics. The results showed that high clay-content Ferrisol exhibited greater aggregate stability than low clay-content Alfisol. The phyllosilicates in Alfisol primarily comprised illite and vermiculite, whereas those in Ferrisol with high-content free-form Fe oxides (Fed) were dominated by kaolinite. Additionally, the clay fraction in Ferrisol contained more aromatic-C than the clay fraction in Alfisol. The 36-year MV incorporation significantly increased the Ferrisol macroaggregate stability (9.57–13.37%), and it also facilitated the transformation of vermiculite into kaolinite and significantly increased the clay, Fed, and aromatic-C contents in Ferrisol. Backscattered electron (BSE)-scanning electron microscopy/energy dispersive X-ray spectroscopy (SEM/EDS) revealed a compact aggregate structure in Ferrisol with co-localization of Fe oxides and kaolinite. Moreover, the partial least path model (PLS-PM) revealed that clay content directly improved macroaggregate stability, and that kaolinite and Fed positively and directly affected clay or indirectly modulated clay formation by increasing the aromatic-C levels. Overall, long-term MV incorporation promotes clay aggregation by affecting mineral transformation to produce more kaolinite and Fe oxides and retain aromatic-C, and it ultimately improves aggregate stability.